Estudantes com deficiência visual na educação de jovens e adultos o emprego de tecnologia assistiva para a aprendizagem conceitual - Junior, Antonio Paulino de Oliveira (Editora Oficina Universitária, 2022)
The book by Antonio Paulino de Oliveira Junior has as its central theme the analysis of the use of Assistive Technology for people with visual impairment in Youth and Adult Education, addressing themes related to the history of Special Education and its intersection with EJA, the concept of disability in the Historical-Cultural Theory, conceptual learning, the function of Assistive Technology throughout the teaching and learning process, as well as the life experience report, which allows the reader to know the unique trajectory of each subject and the objective conditions that outlined their school training process. Assistive Technology resources and services can produce significant results in the effectiveness of school inclusion, allowing people with disabilities greater autonomy and independence, factors which provide them with greater participation and social interaction during teaching activities. In this sense, the author sought to show throughout the work how and which resources could be part of the school's daily life and how and at what moments they are crucial for conceptual learning by students with visual impairments. Every person with a disability is capable of learning and developing, for which an environment with favorable conditions is needed to face the barriers and limitations placed in the structure of social relations and physical spaces, which in many cases stigmatize the person with a disability and reproduce inequality and exclusion of differences.